Meteorological services of Honduras, Guatemala, and Colombia provide more tailored climate services through the use of CCAFS science and tools. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Meteorological services in 3 countries (Colombia, Guatemala, Honduras) provide more tailored climate information to farmers and farmer organizations by adopting novel CCAFS approaches to data curation and seasonal forecasting including R-CPT, predictor domain selection, and RClimTool. A total of 20 staff across the three Meteorological Services in question have been trained to use these new climate prediction and modeling tools. As a result of enhanced integration with the agricultural sector, Colombia pushes a National Framework for Climate Services (NFCS).